2016
DOI: 10.2319/082316-632.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in pharyngeal airway dimensions and hyoid bone position after maxillary protraction with different alternate rapid maxillary expansion and construction protocols: A prospective clinical study

Abstract: Objective: To evaluate the changes in pharyngeal airway dimensions and the position of the hyoid bone after maxillary protraction with different alternate rapid maxillary expansion and construction (Alt-RAMEC) protocols in patients with skeletal class III malocclusion as a result of maxillary retrusion. Material and Methods: The patients with skeletal class III malocclusions were consecutively divided into two groups. Group 1 consisted of 17 patients (11 boys and 6 girls, mean age 11.31 6 1.71 years) who had t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
3
22
1
1
Order By: Relevance
“…Consequently, no significant change was observed in the palatal plane angle. Accordingly, all measurements related to the anterior and posterior face heights increased in agreement with the findings of previous studies 51317…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, no significant change was observed in the palatal plane angle. Accordingly, all measurements related to the anterior and posterior face heights increased in agreement with the findings of previous studies 51317…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, Kaya et al5 protracted the maxilla by using miniplates after the Alt-RAMEC protocol, and they reported a 2-mm forward movement of the A point. In the Alt-RAMEC/FM study of Celikoglu and Buyukcavus,13 a significant increase of 3.34° in the SNA angle was reported. However, only Liou and Tsai4 used a double-hinged expander as in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The posterior rotation of the mandible and the increase of anterior face height could be due to a combination of maxillary vertical movement, maxillary molars extrusion, and chin cup effect of reverse pull headgear. Celikoglu and Buyukcavus[ 16 ] in their study with two different Alt-RAMEC protocols reported similar findings of a significant increase in the maxillary growth, inhibition of mandibular growth, and clockwise rotation of the mandible, leading to an improvement of the maxillomandibular relationship in both groups.…”
Section: Discussionmentioning
confidence: 65%
“…Researchers have used the face mask in various combinations over the years. 3,27,28 Temporary anchorage devices and maxillary protraction applications with direct bone support are recently popular to reduce dentoalveolar effects and increase the skeletal effect. 23,24 There are also applications that perform maxillary protraction with the use of direct miniscrews and inter-miniplates with Class III elastics, as well as successful studies that can be constructed from direct skeletal anchorage using a face mask.…”
Section: Discussionmentioning
confidence: 99%